1996
DOI: 10.1126/science.272.5258.101
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Diarrhea Induced by a Rotaviral Nonstructural Glycoprotein

Abstract: The rotavirus nonstructural glycoprotein NSP4 is an intracellular receptor that mediates the acquisition of a transient membrane envelope as subviral particles bud into the endoplasmic reticulum. NSP4 also causes an increase in intracellular calcium in insect cells. Purified NSP4 or a peptide corresponding to NSP4 residues 114 to 135 induced diarrhea in young (6 to 10 days old) CD1 mice. This disease response was age-dependent, dose-dependent, and specific. Electrophysiologic data from intestinal mucosa showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
507
2
11

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 629 publications
(530 citation statements)
references
References 33 publications
10
507
2
11
Order By: Relevance
“…Ball et al, (1996) have reported that mutation at position 131 has effect on the enterotoxic properties of the protein.…”
Section: Positive Selection At Position 131mentioning
confidence: 99%
See 1 more Smart Citation
“…Ball et al, (1996) have reported that mutation at position 131 has effect on the enterotoxic properties of the protein.…”
Section: Positive Selection At Position 131mentioning
confidence: 99%
“…Initially this 175 aa protein was found to work as a receptor for immature double layered virion entering the endoplasmic reticulum for final maturation (Bergman et al, 1989). Later Ball et al, (1996) demonstrated that purified NSP4…”
Section: Introductionmentioning
confidence: 99%
“…It has also recently been established that rotaviruses, an important cause of diarrhea in young children, produce diarrhea as a consequence of one of their nonstructural proteins, NSP4, stimulating phospholipase C, leading to increased intracellular free Ca 2Ï© in the gut mucosa (18)(19)(20). Thus, it occurred to us that the fluid accumulation in the respiratory tract associated with respiratory infections may be caused by altered epithelial transport.…”
mentioning
confidence: 99%
“…Nonstructural glycoprotein NSP4, encoded by gene segment lOin most strains, has captured much attention since SA 11 NSP4 was reported to induce diarrhea in neonatal mice (2). This viral enterotoxin hypothesis is confirmed and extended by the observation that murine rotavirus NSP4, which is phylogenetically distinct from SA 11 and other mammalian rotavirus NSP4 proteins (4,8), also caused diarrhea in the homologous *Address correspondence to Dr. Osamu Nakagomi, Department of Microbiology, Akita University School of Medicine, 1-1-1 Hondo, Akita, Akita 01(}--8543, Japan.…”
mentioning
confidence: 99%